Hexagonal plate-shaped CuSe nanocrystals by polylol solution chemical synthesis. Issue 181 (13th June 2017) - Ma, Yuanliang; Ji, Huiming; Jin, Zhenggou; Wang, Jian; Zheng, Xuerong; Yuan, Rongsen; Li, Haiqin; Zhao, Suqin
ABSTRACT: (0001)-oriented hexagonal klockmannite CuSe nanoplates were successfully synthesized by polylol solution chemical method, in which triethylene glycol (TEG), triethylenetetramine (TETA) and polyvinylpyrrolidone (PVP) were used as the reaction solvent, reducing agent and capping agent, respectively. The influence of synthesis temperature, TETA adding amounts and refluxing time was mainly investigated.